Cardiovascular simulation using the Finite Element Method - L. C. Sousa (2010)
The purpose of this paper is to develop a numerical computational methodology for steady blood flow simulation in an artery using the Finite Element Method. Due to the complexity of the cardiovascular system simplifying assumptions for the mathematical modelling process are needed. Considering blood flow as an incompressible non-Newtonian flow, the nonlinear state equations are solved for velocity and pressure fields. The upwind-difference method is used for the convective terms. As the compliance of the vascular tissue is not accounted the boundary is considered rigid. The computed artery flow and pressure values for the presented examples are in good agreement with those found in the literature.